Myanmar sanctions : debate intensifies - Kyaw, San Wai. (2012)
The swearing-in of the new government amid a rumoured push by Germany to review EU sanctions against Myanmar has sparked a furore. Sanction supporters have refused to cooperate. This partly reflects the nature of Myanmar’s political players.